OPTIMASI PARAMETER MESIN PRINTER 3D TERHADAP KEKASARAN PERMUKAAN PRODUK MATERIAL ABS MENGGUNAKAN METODE TAGUCHI - Karuniawan, Bayu Wiro; Rachman, Farizi; Yoningtias, Mega Tri (Politeknik Negeri Sriwijaya, Indonesia, 2022)
The examination was directed utilizing 3D Printer FDM (Fused Deposition Modeling) Ender-3 Pro with different mixes of boundaries. Choice of boundaries for 3 kinds of boundaries (Layer level, infill example, and spout temperature), every boundary fluctuated by 3 varieties. The material utilized is ABS (Acrylonitrile Butadiene Styrene) material. The examination strategy utilizes the Taguchi technique. Plan of Experiment involving the Taguchi technique as an orthogonal matrix L9(34) with three replications. The resulting response is only surface roughness. Tests produce the ideal boundaries: layer height 0.1 mm, infill pattern is line pattern and nozzle temperature 240Â°C. The layer height parameter result a contribution percentage of 99,63%, infill pattern 0,04%, and nozzle temperature 0,15%.